Manajemen Edukasi Pendidikan Agama Oleh Pemerintah Gampong Cucum Melalui Kegiatan Festival Anak Sholeh Sebagai Upaya Peningkatkan Pengetahuan Dan Kreativitas Anak Dalam Rangka Memperingati Maulid Nabi - Ira Octavia; Muslem Muslem (Jurnal Riset dan Pengabdian Masyarakat, 2023)
Gampong administration is carried out by people who have been trusted by the community both to lead and take care of all the interests of the gampong. In addition to being responsible for the administration of the gampong, the gampong government is assisted by gampong officials who are also tasked with organizing religious, customary, cultural activities and driving educational and economic programs for the gampong. Gampong community activities, especially in Aceh, cannot be separated from the religious and cultural values ​​in them, one of which is the celebration of the Prophet's Birthday. In the perspective of the Cucum village community, the level of success of the event is assessed from the programs and activities included in the celebration of the Prophet's birthday. The programs and activities that are filled are expected to be able to reflect religious, cultural and customary values ​​in the region, as well as being able to improve the level of education and the village economy. For this reason, the Gampong Cucum government held a competition entitled "Sholeh Children Festival". This festival is a forum for the people of Cucum village to fill the birthday celebration with various kinds of special competitions for children. Simultaneously with the festival, UIN Ar-Raniry students collaborated with the Gampong Government to be involved in sparking and carrying out types of activities at the Sholeh Children Festival. Several competition activities were carried out with the aim of increasing the knowledge and creativity of Cucum village children, namely speech contests, call to prayer, coloring, collages, congregational prayers, nasyid, quizzes, memorizing short letters, tartil, ranking one and marhaban. This type of competition was chosen in accordance with routine religious education activities for children carried out through the Gampong Cucum Government. In this routine activity, the children of Gampong Cucum are educated in the science of reciting, counting, writing and reading. These activities are routinely received by the children in Gampong Cucum from noon to evening. In its implementation, both the Sholeh Children's Festival activities and routine religious education are linked and benefit one another. Children are increasingly motivated in participating in routine religious education as preparation for competitions so that children's interest in learning and knowledge is increasing. On the other hand, the children were more creative and confident in participating in the competition because the preparation was sufficiently mature through routine religious education.